2014
DOI: 10.1124/mol.114.092221
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid and Sodium Butyrate Enhance Natriuretic Peptide Receptor A Gene Transcription: Role of Histone Modification

Abstract: The objective of the present study was to delineate the mechanisms of GC-A/natriuretic peptide receptor-A (GC-A/ NPRA) gene (Npr1) expression in vivo. We used all-trans retinoic acid (ATRA) and histone deacetylase (HDAC) inhibitor, sodium butyrate (NaBu) to examine the expression and function of Npr1 using gene-disrupted heterozygous (1-copy; 1/2), wild-type (2-copy; 1/1), and gene-duplicated heterozygous (3-copy; 11/1) mice. Npr1 1/2 mice exhibited increased renal HDAC and reduced histone acetyltransferase (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 61 publications
1
31
0
2
Order By: Relevance
“…The balance between HAT and HDAC is an essential regulatory switch, which can be achieved through the inhibition of the deacetylation process (17,51). Our previous studies have also demonstrated that Npr1 gene contains various cis-acting elements and both RA and SB enhance its gene transcription and expression (30). Treatment with HB significantly induced cardiac NPRA expression in Npr1 ϩ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance between HAT and HDAC is an essential regulatory switch, which can be achieved through the inhibition of the deacetylation process (17,51). Our previous studies have also demonstrated that Npr1 gene contains various cis-acting elements and both RA and SB enhance its gene transcription and expression (30). Treatment with HB significantly induced cardiac NPRA expression in Npr1 ϩ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mixed esters of butyric acid and retinoic acid hybrid drug (HB) have also been reported to enhance cardiac repair of infarcted hearts in the experimental animals (61,70). In the present study, we examined the effect of RA-, SB-, and HB-mediated effects on the study (30). Control groups were injected with vehicle (DMSO and olive oil).…”
mentioning
confidence: 99%
“…Primers for amplification of Npr1 and β-actin were from Qiagen. PCR amplification was done in triplicate in a 25-µl reaction volume using RT 2 Real-Time SYBR Green/ROX PCR Master Mix and PCR conditions as previously described 78 . Control experiments were done with RNA samples but without reverse transcriptase.…”
Section: Preparation Of Whole Cell Lysate and Nuclear Extract For Wesmentioning
confidence: 99%
“…Because of high lipophilicity, ATRA is thought to be responsible for the slow dissolution and low bioavailability following oral administration [51] , so ATRA (500 μg/kg body weight) was dosed intraperitoneally. This dose of ATRA was selected on the basis of existing data [52,53] . In vivo, retinol is the major source of RA and RALDH is identified as an RA-generating enzyme [54] .…”
Section: Discussionmentioning
confidence: 99%